2006
DOI: 10.1002/anie.200503726
|View full text |Cite
|
Sign up to set email alerts
|

Functional‐Group Chemistry of Organolithium Compounds: Photochemical [2+2] Cycloaddition of Alkenyl‐Substituted Lithium Cyclopentadienides

Abstract: Li and light: Alkenyl‐substituted lithium cyclopentadienides, which are in equilibrium with the substituted lithocene anion structure 1, undergo a photochemical [2+2] cycloaddition to yield selectively the carbon–carbon coupling product 2. This is a rare case of organic functional‐group chemistry for a reactive organolithium compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 46 publications
(17 reference statements)
0
8
0
Order By: Relevance
“… 170 A related behavior was observed for alkenyl-substituted lithium cyclopentadienides. 173 Even a ladderane structure could be generated by employing a bis(butadienylcyclopentadienyl)zirconium complex. 174 Iwama et al showed that intramolecular [2 + 2] photocycloaddition reactions are possible between two double bonds in bridged bis(azulenyl) zirconocenes.…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“… 170 A related behavior was observed for alkenyl-substituted lithium cyclopentadienides. 173 Even a ladderane structure could be generated by employing a bis(butadienylcyclopentadienyl)zirconium complex. 174 Iwama et al showed that intramolecular [2 + 2] photocycloaddition reactions are possible between two double bonds in bridged bis(azulenyl) zirconocenes.…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
“…The Erker group employed this concept for the synthesis of novel ansa -metallocenes. The bis­(2-alkenylindenyl)zirconium complex 69 for example gave upon direct excitation the cyclobutylene-bridged zirconocene 70 in a yield of 50% (Scheme ). A related behavior was observed for alkenyl-substituted lithium cyclopentadienides . Even a ladderane structure could be generated by employing a bis­(butadienylcyclopentadienyl)zirconium complex .…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
“…Furthermore, cycloreversion reactions have also been widely investigated because of their practical and theoretical potentials . In particular, electron-transfer-induced [2 + 2] cycloaddition reactions have extensively been studied . In order to generate radical ion intermediates, photochemical processes are widely employed .…”
Section: Introductionmentioning
confidence: 99%
“…One calcium atom (Ca1) is attached to the Cp ring of a fluorene skeleton. The distances between Ca1 and carbon atoms in the Cp ring have a narrow range from 2.738(3) to 2.776(3) Å, indicating an η 5 mode interaction . Ca1 also coordinates with an exocyclic oxygen atom (O1) of another fluorene skeleton.…”
Section: Resultsmentioning
confidence: 99%